2020
DOI: 10.1101/2020.11.13.20231316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the Panbio™ rapid antigen test for SARS-CoV-2 in primary health care centers and test sites

Abstract: BackgroundRapid antigen tests (Ag-RDT) are emerging as new diagnostic tools for COVID-19 and real-world evaluations are needed to establish their performance characteristics.Main objectiveTo evaluate the accuracy of the Panbio™ Ag-RDT at primary health care (PHC) centers and test sites in symptomatic patients and close contacts, using the Reverse-Transcription Polymerase Chain Reaction (RT-PCR) test as the gold standard.MethodsThis was a prospective diagnostic study conducted in four PHC centers and two test s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 16 publications
8
42
4
2
Order By: Relevance
“…[ 5 ] most participants (70.6%) were tested within 5 days of exposure. Sensitivity of the Panbio™ test was lower than was previously found [ [3] , [4] , [5] , [6] ] in symptomatic patients (around 80%), yet as reported for the latter patients, RAD sensitivity was directly related to the magnitude of SARS-CoV-2 RNA load in NP specimens. Such a striking difference might reflect dissimilarities across symptomatic and asymptomatic individuals in the kinetics of SARS-CoV-2 load in the upper respiratory tract [ 8 , 9 ].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…[ 5 ] most participants (70.6%) were tested within 5 days of exposure. Sensitivity of the Panbio™ test was lower than was previously found [ [3] , [4] , [5] , [6] ] in symptomatic patients (around 80%), yet as reported for the latter patients, RAD sensitivity was directly related to the magnitude of SARS-CoV-2 RNA load in NP specimens. Such a striking difference might reflect dissimilarities across symptomatic and asymptomatic individuals in the kinetics of SARS-CoV-2 load in the upper respiratory tract [ 8 , 9 ].…”
Section: Discussioncontrasting
confidence: 59%
“…(45.4%) [ 5 ] and Bulilete et al. (59.0%) [ 6 ], in apparently comparable cohorts. However, in two of these studies [ 4 , 5 ], the RAD test was carried out at a central laboratory, and timing of sample collection was not disclosed [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Several jurisdictions use the Panbio Ag Rapid Test Device to identify positives early, assuming that negative results should be confirmed [ [34] , [35] , [36] ]. One recent study showed that none of those who were test discordant (positive by RT-PCR but negative using Panbio) had culturable virus in their sample [ 34 ], indicating potentially reduced transmissibility by individuals defined as “false negatives” in current protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 8, 2020. ; https://doi.org/10.1101/2020.12.07.20239558 doi: medRxiv preprint RT-LAMP vs. RT-PCR -Manuscript 10 jurisdictions are exploring use of PanBio Ag Rapid Test Device to identify positives early, assuming that negative results will need additional testing in order to be confirmed [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%